Investigation of ground vibrations induced by trains moving on saturated transversely isotropic ground. Issue 104 (January 2018) - Gao, Guangyun; Xu, Chenxiao; Chen, Juan; Song, Jian
Abstract: A 2.5D FEM (finite element method) is used to investigate the effects of soil parameters of transversely isotropic (cross anisotropic) saturated soil on ground vibrations and excess pore water pressures induced by moving train loads. The governing equations of transversely isotropic saturated soil are derived from the Boit's theory in frequency domain by applying the Fourier transform with respect to time, and 2.5D FE model is then established using Galerkin method. Correctness of the proposed model is validated with published data. Numerical results illustrate that the decrement of vibration amplitude and excess pore water pressure caused by the increment of vertical elastic modulus is more significant than that of the horizontal direction. Poisson ratios in both directions have little effect on ground vibrations, while an increase in horizontal Poisson ratio results in a significant increment in excess pore water pressure. Highlights: The u - p format 2.5D FEM model in transversely isotropic medium is deduced. Ground vibration is computed under high-speed train loads. Effects of moduli and Poisson ratios on vertical ground vibration are analyzed. Effects of moduli and Poisson ratios on pore water pressure are analyzed.